Environmental dynamic, business strategy, and financial performance: An empirical study of Indonesian property and real estate industry - Imam Wahyudi (The South East Asian Journal of Management, 2013)
Firm’s strategic orientation involves synchronizing environmental dynamics, corporate strategy and capital structure in order to achieve firm performance targets. The co-alignment model used successfully in the hospitality industry might be used in a wider context as a framework in explain- ing these relationships simultaneously. Using the data of public firms in Indonesia during the pe- riod of 1996-2010, we found that co-alignment model can be implemented in property and real estate industry as well as in hospitality industry.